Structure‐Guided Design of a Group B Streptococcus Type III Synthetic Glycan–Conjugate Vaccine. Issue 31 (1st April 2020) - Oldrini, Davide; del Bino, Linda; Arda, Ana; Carboni, Filippo; Henriques, Pedro; Angiolini, Francesca; Quintana, Jon I.; Calloni, Ilaria; Romano, Maria R.; Berti, Francesco; Jimenez‐Barbero, Jesus; Margarit, Immaculada; et al.
Abstract: Identification of glycan functional epitopes is of paramount importance for rational design of glycoconjugate vaccines. We recently mapped the structural epitope of the capsular polysaccharide from type III Group B Streptococcus (GBSIII), a major cause of invasive disease in newborns, by using a dimer fragment (composed of two pentasaccharide repeating units) obtained by depolymerization complexed with a protective mAb. Although reported data had suggested a highly complex epitope contained in a helical structure composed of more than four repeating units, we showed that such dimer conjugated to a carrier protein with a proper glycosylation degree elicited functional antibodies comparably to the full‐length conjugated polysaccharide. Here, starting from the X‐ray crystallographic structure of the polysaccharide fragment–mAb complex, we synthesized a hexasaccharide comprising exclusively the relevant positions involved in binding. Combining competitive surface plasmon resonance and saturation transfer difference NMR spectroscopy as well as in‐silico modeling, we demonstrated that this synthetic glycan was recognized by the mAb similarly to the dimer. The hexasaccharide conjugated to CRM197, a mutant of diphtheria toxin, elicited a robust functional immune response that was not inferior to the polysaccharide conjugate, indicating that it may suffice as a vaccine antigen. This is the first evidence of an X‐ray crystallography‐guided design of a synthetic carbohydrate‐based conjugate vaccine. Abstract : Deciphering the sugar glycocode : Starting from the X‐ray crystallographic structure of a fragment from Group B Streptococcus type III capsular polysaccharide in complex with a protective mAb complex, a hexasaccharide comprising exclusively the relevant positions involved in interactions was obtained. By structural and immunogenicity studies it was shown that the synthetic hexasaccharide recognized the mAb similarly to the polysaccharide fragment and, conjugated to a carrier protein, suffices as vaccine antigen.